Ost-West-Wanderung in Europa - Fassmann, Heinz (2000)
The years 1989/1990 saw the fall of the Iron Curtain. Following forty years of significant restrictions, legal and non-bureaucratic travel from East-Central and Eastern European countries was once again possible and travelling and returning to those countries became just as easy. Immediately following the end of the East-West conflict, people from East-Central and Eastern European countries took advantage of their new freedom of travel. Many sought to emigrate to Western countries. However, when faced with such immigration, the euphoria which met the end of the political divisions in the West evaporated quickly. Several polls and surveys, projections and prognoses served to unsettle people more than the reality of immigration. This gave rise to a sometimes blind and specious - yet nevertheless politically effective - fear of a new mass migration of peoples. Now, more than ten years after the fall of the Iron Curtain, the actual scale and development of the East-West migration in Europe be clearly evaluated. This book attempts to do just that, including a comprehensive overview and eleven country-specific chapters. Each chapter includes a historical review, an account of the most important changes since 1989/1990 and a forecast of future migration developments.